The intra-S phase checkpoint targets Dna2 to prevent stalled replication forks from reversing - Hu, Jiazhi; Sun, Lei; Shen, Fenfen; Chen, Yufei; Hua, Yu; Liu, Yang; Zhang, Mian; Hu, Yiren; Wang, Qingsong; Xu, Wei; Sun, Fei; Ji, Jianguo; et al. (Cell, 2012)
When replication forks stall at damaged bases or upon nucleotide depletion, the intra-S phase checkpoint ensures they are stabilized and can restart. In intra-S checkpoint-deficient budding yeast, stalling forks collapse, and ∼10% form pathogenic chicken foot structures, contributing to incomplete replication and cell death (Lopes et al., 2001; Sogo et al., 2002; Tercero and Diffley, 2001). Using fission yeast, we report that the Cds1(Chk2) effector kinase targets Dna2 on S220 to regulate, both in vivo and in vitro, Dna2 association with stalled replication forks in chromatin. We demonstrate that Dna2-S220 phosphorylation and the nuclease activity of Dna2 are required to prevent fork reversal. Consistent with this, Dna2 can efficiently cleave obligate precursors of fork regression-regressed leading or lagging strands-on model replication forks. We propose that Dna2 cleavage of regressed nascent strands prevents fork reversal and thus stabilizes stalled forks to maintain genome stability during replication stress.